2006
DOI: 10.1155/ijp/2006/48462
|View full text |Cite
|
Sign up to set email alerts
|

EPR and Fluorescence Spectroscopy in the Photodegradation Study of Arabian and Colombian Crude Oils

Abstract: EPR and fluorescence spectroscopy were used to evaluate the degradation of crude oils of different origins that were submitted to photochemical weathering under tropical conditions. The EPR spectra obtained showed signals of the paramagnetic species: the vanadylVO2+ion and organic free radicals. A decrease in linewidth of free radical signals was observed for both oils irradiated for 100 hours with sunlight of 350 W/m2. The reduction in the linewidth of the free radical of 9.8% in Arabian oil and 18.5% in Colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
1
7
1
1
Order By: Relevance
“…The diversity of g -values in oil disperse systems is, among other reasons, attributed to the spin–orbit coupling of unpaired electrons and the existing heteroatoms. The value of the g -factor is higher than typical values reported in the literature (see refs and and the Introduction section), reflecting the low aromaticity in the environment of the free radical in the high-molecular components of the oil under study. Furthermore, the presence of phenoxy radicals partially localized in aromatic systems due to the oxygen might be the reason for the observed high value of the g -factor. , …”
Section: Resultscontrasting
confidence: 50%
“…The diversity of g -values in oil disperse systems is, among other reasons, attributed to the spin–orbit coupling of unpaired electrons and the existing heteroatoms. The value of the g -factor is higher than typical values reported in the literature (see refs and and the Introduction section), reflecting the low aromaticity in the environment of the free radical in the high-molecular components of the oil under study. Furthermore, the presence of phenoxy radicals partially localized in aromatic systems due to the oxygen might be the reason for the observed high value of the g -factor. , …”
Section: Resultscontrasting
confidence: 50%
“…Figure 1) centered at 3454 G, characterized by a g value of 2.0035 and the ΔH p-p of 5.1 G. The parameters of the spectrum recorded were consistent with the radical species observed in the crude oil and originating from asphaltene species. 20,21 The spin number of detected radicals (6.7 × 10 18 spins/g of sample) was in the range of the number of radicals present in pure asphaltenes. 22 Unlike other reports, no spectral features were observed typical for the presence of metal centers, often present in asphaltenes from crudes.…”
Section: Resultsmentioning
confidence: 93%
“…In different studies of oil dispersed in seawater, it was found that the synchronous fluorescence decreased with irradiation [8][9][10][11]. Photochemical weathering of Brazilian petroleum was evaluated by using EPR spectroscopy showing a partial destruction of the asphaltenic fraction of the oil [12].…”
Section: Introductionmentioning
confidence: 99%